MARKETING TURÍSTICO Y SU EFECTO EN EL DESARROLLO ECONÓMICO DEL CANTON BALZAR, AÑO 2022 - ZAMBRANO MACIAS, DAYANA ELIZABETH (2022)
The purpose of this research work is to carry out a tourist marketing and its effect on the economic development of the Balzar canton, said information that will serve to promote the tourist attractions that the canton has. In this investigative work, we seek to identify the attractions that the Balzar canton currently offers and the corresponding promotion strategies that it currently has, since one of them would be social networks. The methodology that was used was the descriptive and bibliographic method, which helped to identify the attractions that the canton has, likewise, the promotion strategy that I apply for tourism, above all, it helped to know the importance that tourism influences in the economic field. One of the applied techniques were the surveys since this helped to know the activities carried out by the municipal Gad to generate economic income such as: the Daule river regatta, Gastronomic Fairs, El Rodeo Montubio among others. Thus, generating tourist influx and above all economic income and generating employment for the inhabitants of the Balzar canton. The technique of the interview conducted with the head of the tourism department, Mr. Deyber Carreño Alcívar, was also used, with his information it was possible to analyze the strategies that he implements to improve the tourism sector.